A Plea For Coalition of the Quantifiable and the Non-Quantifiable Approaches to Management - Dale, Ernest (Academy of Management Journal, 1969)
This article presents a speech by Ernest Dale, president of the Wharton School of Finance and Commerce at the University of Pennsylvania, delivered at the 28th annual meeting of the Academy of Management that was held in Chicago, Illinois on December 28, 1968. Conducting a study of the impact of computerization on management, Dale found that many top managers were concerned about the tendency of their middle managers to allow the computers to dictate their decision. He discusses some of the major issues with the scientific approach to management. Several assumptions concerning various approaches to management are highlighted.